Implementasi Filosofi Pendidikan Indonesia Abad Ke-21 Di Sekolah Menengah Atas: Tantangan Dan Strategi - Lisbet Ariati Rumahorbo; Liesna Andriany (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
Education in Indonesia has undergone major changes since the beginning of the 21st century, with an emphasis on a student-centered educational paradigm and learning adapted to the needs of the times. At the beginning of the 21st century, there have been significant and undeniable advances in technology. Humans have utilized their inherent potential to face the challenges posed by nature through technological means. This article discusses the challenges and strategies for implementing 21st century Indonesian educational philosophy in secondary schools. The main challenges faced are resistance to change, lack of understanding of philosophical concepts, and limited resources. However, to overcome these challenges requires a training and coaching approach for educators, integrating educational philosophy into the curriculum and extracurricular activities, as well as various approaches to support the implementation of Indonesian educational philosophy in the 21st century. Through strong efforts and collaboration between various stakeholders, the implementation of the 21st century Indonesian education philosophy in secondary schools is expected to produce graduates who have qualities, values and skills that are in line with the needs of the times.